Protocol for a randomised phase 3 trial evaluating the role of Finasteride in Active Surveillance for men with low and intermediate-risk prostate cancer: the FINESSE Study - Cumberbatch, Marcus; North, Bernard; Kealy, Roseann; Smith, Samuel; Hubbard, Rachel; Kennish, Steven; Bhattrai, Selina; Cross, William; Chahal, Rohit; Bryant, Richard; Lamb, Alastair D; Dooldeniya, Mohantha; et al. (BMJ open, 2025)
BackgroundProstate cancer (PCa) is the most common male malignancy in the western world. Many men (40%) are diagnosed with localised low or intermediate-risk PCa, which is suitable for active surveillance (AS). AS affords careful monitoring to identify changes in otherwise non-life-threatening cancers. While AS reduces overtreatment (and quality of life impact), long-term compliance can be poor, with many men undergoing radical treatment after starting AS.Methods and analysisFinasteride in Active Surveillance for men with low and intermediate-risk prostate cancer (FINESSE) is a prospective, open-label, two-arm, phase 3 trial, in which men with low or intermediate PCa are randomised (1:1) to receive AS with or without finasteride (5 mg once a day for 2 years). Randomisation is stratified by age and PCa risk. AS includes regular prostate-specific antigen testing, MRI scans and the offer of repeat biopsy (at 3 years, or if imaging suggests progression). Additional MRI scans and/or biopsies will be performed for biochemical or clinical indications. We aim to recruit 550 men (aged 50 to 75 years) from up to eight sites. Active outpatient follow-up will be for 3–5 years (depending on date recruited), followed by passive registry-based follow-up for up to 10 years. Primary outcome is adherence to AS. Secondary outcomes include rates and type of disease progression, treatments received (for PCa and benign prostatic enlargement), overall and PCa-specific mortality, an understanding of patients/professionals views of this approach and health-related quality of life. An external panel of experts blinded to allocation will review all AS cessation and progression events. Trial pathologist’s and radiologist’s, blinded to allocation, will review representative cases. Analysis is Intention to Treat.Ethics and disseminationThe study received Health Research Authority and South-Central Oxford Research Ethics Committee (14/12/2021: 21/SC/0349) and CTA/MHRA (29/12/2021: 21304/0274/001–0001) approvals. Results will be made available to providers and researchers via publicly accessible scientific journals.Trial registration number ISRCTN16867955